The rule of law and sustainability of the constitution: The case of tax evasion - Nadeem Naqvi; Bernhard Neumärker; Gerald Pech (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2012)
Why do rulers play by the rules? We show that the legality requirement under the rule of law implements an endogenous enforcement mechanism supporting constitutionality. Agents which do not obey unconstitutional legal norms are not sanctioned under constitutional rule. A principal who defects from the constitution but cannot commit himself to never reinstall the constitution finds law enforcement more difficult. As more agents disobey, enforcement becomes less effective. The expectation of an eventual return to constitutionality becomes self-fulfilling. We show this mechanism to be effective in deterring a government from violating constitutional norms.
Keywords: D78; K10; K42; H26; 330; constitution; dynamic policy constraints; tax evasion; global games